Are Jordan and Tunisia's Exports Becoming More Technologically Sophisticated? And Why It Matters - Diop, Ndiame; Ghali, Sofiane (World Bank, Washington, DC, 2012)
The last decade has witnessed two interesting features in international trade. First, high-tech products have become the fastest growing segment of international trade. Second, developing countries are increasingly becoming exporters of high-tech products thanks to greater trade openness, greater ability to master and use technologies, and a rise in foreign direct investments. The objective of this paper is to pinpoint the changes in Jordan and Tunisia's production and export structures over the last decade or so. Authors were use two highly disaggregated panel export database and a 'product-based' methodology that allows a mapping of products classified by technological content and their sector of origin. The database used runs from 2003 to 2010 for Jordan and from 1995 to 2009 for Tunisia, providing a pseudo-panel structure. Finally, improving the environment for innovation may facilitate the movement up the technological ladder in both Jordan and Tunisia.